Gambaran Gaya Hidup Sedentari Pada Remaja Putri Di Pondok Pesantren Darul Aman Gombara Makassar - Andi Aisyah; Rahayu Indriasari; Sabaria Manti Battung; Healthy Hidayanty; Veni Hadju (Departement of Nutrition, Faculty of Public Health, Hasanuddin University, Makassar, 2021)
Introduction: In adolescence nutritional conditions are very important to support their growthand development. Nutrition problems that usually occur in adolescents are caused by severalfactors such as the level of nutritional knowledge that will affect their behavior and lifestyle suchas sedentary activity, screen time duration, and also sleep duration especially for adolescent whoattend school in islamic boarding school. Purpose: This study aims to know the description ofsedentary lifestyle which includes sedentary activity and sleep duration of adolescent girls inIslamic Boarding School Darul Aman Gombara Makassar. Materials and Methods: The type ofthis study is descriptive. The sample of this study was 96 adolescents using total sampling.Collecting data for sedentary activity using the recall activity questionnaire, and for the sleepduration using STQ (Sleep Timing Questionnaire). Data pricessing and analysis in this studyusing SPSS. Result: The results of the analysis for sedentary activity found that 27,1% ofrespondents sedentary, and 72,9% of respondents not sedentary. As for sleep duration on